Experimental and theoretical investigation of mechanical behavior related to temperature, humidity and strain rate on silane-modified polyurethane sealant - Jun Zhang; Hao zhong Shen; Xin Zhang; Hai yu Li (Polymer Testing, 2021)
In order to investigate the effects of temperature, humidity and strain rate on the mechanical properties of silane-modified polyurethane sealant, the humidity experiments and uniaxial tensile experiments at different testing conditions were conducted. The experimental results indicate that the mechanical properties exhibit nonlinear and dependence on temperature, humidity and strain rate. However, it exhibits rate independence at higher temperature and higher degree of humidity. The degree of humidity of the material is related to the immersion temperature and immersion time in the water bath. Furthermore, it is also observed that the tensile strength, elastic modulus and fracture strain of the materials are sensitive to the temperature, humidity and strain rate. Considering the effects of temperature, humidity and strain rate, a nonlinear constitutive model is developed to describe the tensile deformation behavior of the silane-modified polyurethane sealant. Comparisons between the model calculated and the experimental results show that the developed model has an accurate description to the tensile deformation behavior of the silane-modified polyurethane sealant under different testing conditions.